The Value Added Statement: A Review of Its Use in Corporate Reports (Book). - Hendriksen, Eldon S.; Burns, Thomas J. (The Accounting Review, 1979)
Reviews the book "The Value Added Statement: A Review of Its Use in Corporate Reports," by Michael F. Morley.